Pengaruh Pengawasan, Disiplin Kerja dan Reward Terhadap Kinerja Pegawai pada Kantor Walikota Medan Divisi Perencanaan dan Keuangan - Tiara Indah; Eka Purnama Sari (Pusat Riset dan Inovasi Nasional, 2023)
In general, every company or agency prioritizes the good performance of its employees. Good performance can advance the company in terms of time and completeness of work. The problem faced is that some employees are not disciplined in carrying out their duties and obligations. Given the performance of employees who are still far from expected because there are still some employee expectations that have not been met. The problem that occurs is that supervision is not carried out routinely and is not attentive. Given that supervision is still far from what was expected because there are still some expectations of supervision that have not been fulfilled. So this can affect employee performance. The problem at issue is that the reward does not meet employee satisfaction. Considering that the reward is still far from what was expected because there are still several expectations for the reward that have not been fulfilled. So that this can affect the performance of employees. This research is a quantitative research with associative method. Based on the results of the SPSS test on Anova data in column R Square = 0.921, all variables affect the Employee Performance Variable by 92.1% and the remaining 7.9% is influenced by other variables outside this regression equation or variables not examined. So it can be concluded that the specified variable is very influential on employee performance.